2019
DOI: 10.9734/irjpac/2019/v18i230083
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of Newer Insecticides against Spotted Pod Borer [Maruca vitrata (Geyer)], on Blackgram (Vigna mungo L.) in North Coastal Andhra Pradesh

Abstract: Aims: To evaluate the efficacy of novel insecticides against the spotted pod borer on rice fallow blackgram. Study Design: Randomised Block Design (RBD) was used in this study. Place and Duration of Work: The present study was carried out at College farm Agricultural College, Naira during Rabi 2017-2018 season. Methodology: The spotted pod borer, Maruca vitrata (Geyer) is a serious pest of blackgram through out the growth period especially in flowering and pod development stages in North Coas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…These findings are in conformity with those of Bhusal and Bhattarai (2019) with cholarantraniliprole. Swathi et al (2019) observed that chlorantraniliprole 9.3% + lambda cyhalothrin 4.6% @ 0.5 ml/ l was very effective on M. vitrata. Kamble et al (2014) revealed that indoxacarb 14.5SC + acetamiprid 77SC gave significantly more yield of healthy fruits of okra followed by profenophos 40EC + cypermethrin 4EC and chlorpyriphos 50EC + cypermethrin 5EC reducing Earias vitella infestation.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…These findings are in conformity with those of Bhusal and Bhattarai (2019) with cholarantraniliprole. Swathi et al (2019) observed that chlorantraniliprole 9.3% + lambda cyhalothrin 4.6% @ 0.5 ml/ l was very effective on M. vitrata. Kamble et al (2014) revealed that indoxacarb 14.5SC + acetamiprid 77SC gave significantly more yield of healthy fruits of okra followed by profenophos 40EC + cypermethrin 4EC and chlorpyriphos 50EC + cypermethrin 5EC reducing Earias vitella infestation.…”
Section: Resultsmentioning
confidence: 88%
“…The highest benefit cost ratio was obtained with thiamethoxam 12.6 + lambda cyhalothrin 9.5% ZC (1:28.33) followed by chlorantraniliprole 9.3 % + lambda cyhalothrin 4.6%ZC (1:20.00) and others. Swathi et al, (2019) reported that chlorantraniliprole 9.3% + lambdacyhalothrin 4.6% @ 0.5 ml/ l followed by chlorantraniliprole 18.5SC @ 0.0037% and flubendiamide @ 39.35SC 0.00787% led to least pest incidence in pigeonpea but highest cost: benefit (C:B) ratio 1: 17.14 was recorded from chlorantraniliprole 18.5SC and spinosad 45SC.…”
Section: Resultsmentioning
confidence: 99%